Severe Refractory Paraneoplastic Mucous Membrane Pemphigoid Successfully Treated With Rituximab - Wittenberg, Marcel; Worm, Margitta (Frontiers in Medicine, 2019)
A 67-year-old man treated for a prostate cancer in 2016 presented to our clinic with sore throat, intraoral bullae, odynophagia, dysphonia, exertional dyspnoea and erosions of the glans penis. Clinical examination confirmed a laryngo-pharyngitis with involvement of the epiglottis. Despite repeated pulse therapies with steroids and a combined systemic treatment with prednisolone and either dapsone or azathioprine, a progress of the disease with ocular involvement and onset of synechia of the vocal cords leading to acute dyspnoea occurred. Diagnosis of paraneoplastic MMP initially was made by clinical criteria followed by histological and serological confirmation. Two month after initiation of rituximab therapy complete disease control was achieved.